Fresno-Merced Counties Legal Services' Farewell Dinner For Tony White - Watkins, Howard::::::::: (1983)
Mary Ludy, Kathy Reilley, Mary Beth Riday, Tony White, Nancy Marsh, Howard Watkins, Christine Watkins, Janie Munoz, Gloria Escalante, Virginia Salmeron, Genie Baranoff, Janice Pearson, Leroy Cordova, Alicia Gutierrez, Christine Burnes, David Burnes, Doris Burnes